2022
DOI: 10.3389/fpubh.2022.777567
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic and Comparative Review of Behavior Change Strategies in Stress Management Apps: Opportunities for Improvement

Abstract: Stress is one of the significant triggers of several physiological and psychological illnesses. Mobile health apps have been used to deliver various stress management interventions and coping strategies over the years. However, little work exists on persuasive strategies employed in stress management apps to promote behavior change. To address this gap, we review 150 stress management apps on both Google Play and Apple's App Store in three stages. First, we deconstruct and compare the persuasive/behavior chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 105 publications
0
9
0
Order By: Relevance
“…However, Ferdous and colleagues [ 28 ] found that patterns of smartphone app usage were correlated with stress levels in work environments and thus recommended that these could be used to measure stress at work. Alhasani et al [ 29 ] presented the possibility of an app that creates behavioral data, based on self-report and sensors, that can be analyzed in real-time to predict users’ needs and provide tailored interventions for the user. In the case of rural health workforce capability, if a health professional’s heart rate variability indicates high stress levels derived from a sensor, the app can recommend a predetermined meditation session.…”
Section: Discussionmentioning
confidence: 99%
“…However, Ferdous and colleagues [ 28 ] found that patterns of smartphone app usage were correlated with stress levels in work environments and thus recommended that these could be used to measure stress at work. Alhasani et al [ 29 ] presented the possibility of an app that creates behavioral data, based on self-report and sensors, that can be analyzed in real-time to predict users’ needs and provide tailored interventions for the user. In the case of rural health workforce capability, if a health professional’s heart rate variability indicates high stress levels derived from a sensor, the app can recommend a predetermined meditation session.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a co-design approach to these tools with students should be emphasized to better target their needs and increase their adherence to the developed stress management programs (Amanvermez et al, 2021). Furthermore, to maintain user engagement and to produce this change that would lead to better management of their stress, the interface of these devices must be visually attractive and easy to use, organized, and free of ambiguous features (Oyebode et al, 2020;Alhasani et al, 2022).…”
Section: Coping Strategies Used By the Female Students In The Academi...mentioning
confidence: 99%
“…Reviews already exist; however, they all focus on specific aspects and some might be outdated. Pre-existing SMA reviews focus on content alone [ 31 , 32 ], content in combination with transparency and functionality [ 33 ], efficacy [ 34 ], gamification elements [ 35 ], persuasive and behavior change strategies [ 36 ], or quality of apps, with a focus exclusively on mindfulness apps [ 37 ]. Regarding content, it was shown that mindfulness and meditation were the most commonly used strategies in the reviewed SMAs (34% to 78% of all apps included these strategies) [ 31 , 33 , 34 ], followed by breathing [ 31 , 33 ] or goal setting [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding content, it was shown that mindfulness and meditation were the most commonly used strategies in the reviewed SMAs (34% to 78% of all apps included these strategies) [ 31 , 33 , 34 ], followed by breathing [ 31 , 33 ] or goal setting [ 34 ]. Further common strategies were personalization and self-monitoring, while social support strategies were rarely used [ 36 ]. The implementation of gamification elements is relatively scarce (on average 0.5 elements per app) [ 35 ].…”
Section: Introductionmentioning
confidence: 99%